Optimalisasi Transformasi Digital Berbasis Kearifan Lokal untuk Pemberdayaan Komunitas dan Keberlanjutan Sosial - Maria Atik Sunarti Ekowati; Kristyana Dananti; Sri Wening (Forum Kerjasama Pendidikan Tinggi, 2026)
Digital transformation has become a key catalyst in improving community quality of life, yet its implementation often neglects cultural context and local wisdom. This study aims to develop a conceptual framework for community empowerment based on digital technology integrated with cultural values, thereby fostering social and economic sustainability. The method employed is Community-Based Participatory Research (CBPR), with a case study of a village community in Surakarta engaged in digital literacy and creative economy development. The program stages include: needs assessment and local potential mapping, digital literacy training, mentoring of MSMEs in technology adaptation, integration of cultural narratives into digital products, and sustainability evaluation through socio-economic indicators. The program was conducted over six months (September 2025–February 2026) in Sukamaju Village, Karanganyar. Results indicate significant improvements before and after program implementation: enhanced digital capacity, increased number of MSMEs entering digital markets, higher community income, and stronger cultural identity preservation. These findings confirm that optimizing the integration of technology with local wisdom not only strengthens digital capacity but also reinforces cultural identity, expands economic opportunities, and builds social resilience. The conclusion highlights that digital transformation rooted in local values creates inclusive, relevant, and sustainable social innovation. The CBPR-based empowerment model proved adaptive to digital disruption while strengthening a resilient socio-economic ecosystem. This research contributes to evidence-based policymaking for local governments, academics, and communities, emphasizing that social sustainability requires not only technology adoption but also the utilization of local values as its foundation.